Association between COVID-19 history and postoperative delirium in elderly patient undergoing elective surgery: a prospective, two-center observational cohort study - Duan, Wen; Yang, Jin-Jin; Fang, Pan-Pan; Zhu, Wen-Jie; Zhang, Yue; Li, Xin-Yu; Ma, Da-Qing; Shan, Yang-Yang; Liu, Xue-Sheng; Yang, Jian-Jun (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Purpose An increased incidence of delirium was reported in patients especially in elderly patient during the acute phase of coronavirus disease 2019 (COVID-19). However, whether COVID-19 history increases the risk of postoperative delirium (POD) in elderly patients remains unclear. This study aims to investigate the association between COVID-19 history and POD in elderly patients undergoing elective surgeries. Methods In this prospective, two center cohort study, 500 elderly patients undergoing elective surgeries from March to May 2023 were analyzed. The primary exposure was a history of COVID-19. The primary outcome was POD assessed with 3-min diagnostic confusion assessment method or confusion assessment method for the intensive care unit within three days after surgery. We used inverse probability of treatment weighting (IPTW) to balance the differences between patients with or without a history of COVID-19. The association between COVID-19 history and POD was estimated using a logistic regression model with IPTW. Additionally, we next exploringly conducted subgroup analysis and assessed interaction effects to evaluate the impact of COVID-19 history on POD based on frailty/pre-frailty, cancer, surgical type/classification, sex, profession, and residence type. Results In this cohort, 412 patients had a history of COVID-19 with an incidence 16% of POD while 88 were uninfected with 15.9% of POD incidence. There was no association between COVID-19 history and POD [adjusted odds ratio (OR adj ) 1.20 (0.80–1.79), P = 0.378] in elderly patients undergoing elective surgery. However, POD was significantly increased in patients with COVID-19 history who were pre-frailty/frailty or with cancers [OR adj 2.41 (1.19–5.10) and OR adj 2.29 (1.23–4.39), respectively]. Conclusion This preliminary exploratory study found no association between a history of COVID-19 and POD in elderly patients undergoing elective surgery. Trial registration Registered at the Chinese Clinical Trial Center ( https://www.chictr.org.cn/showproj.html?proj=192846 ) with No. ChiCTR2300069308 on Mar 13, 2023.